INTERCULTURALISM IN MIDDLE EASTERN LITERATURE: REPRESENTATION OF IDENTITY, CULTURAL CONFLICT, AND INTERCULTURAL AWARENESS - Khomisah Khomisah (Arabic Literature Department, 2026)
This study addresses the increasing need for cross-cultural understanding in the era of globalization, where interactions among diverse cultural groups have intensified. Focusing on Middle Eastern studies, this research examines literature as a cultural medium that facilitates intercultural dialogue. The study aims to analyze how literary works by Middle Eastern authors represent cultural interactions and mediate intercultural communication. This research employs a library research method with a qualitative content analysis approach, focusing on themes of identity, cultural representation, and intercultural conflict in selected Middle Eastern literary texts and related scholarly works. The analysis demonstrates that these literary works reflect complex encounters between tradition and modernity, as well as between local and global cultural influences, particularly in contexts shaped by migration and historical transformation. The findings indicate that Middle Eastern literature not only represents social realities but also promotes intercultural awareness by portraying characters engaged in identity negotiation and cultural tension. These narratives foster empathy and understanding across cultural boundaries. The study concludes that literature serves as an effective medium for strengthening intercultural discourse and offers a valuable contribution to multicultural education from the perspective of Middle Eastern literature.